Mad world : Evelyn Waugh and the secrets of Brideshead - Byrne, Paula (New York : Harper, 2010)
'A terrifically engaging and original biography of Evelyn Waugh and the family that provided him with the most significant friendships of his life and inspired his masterpiece, BRIDESHEAD REVISITED'--Provided by publisher.
Includes bibliographical references (p. 350-354) and index.
Keywords: Waugh, Evelyn, -- 1903-1966.; Waugh, Evelyn, -- 1903-1966.; Authors, English -- 20th century -- Biography